Tobacco Control Policy in the Netherlands Between Economy, Public Health, and Ideology - Willemsen, Marc C. (Palgrave Studies in Public Health Policy Research, 2018)
tobacco control; policy process; advocacy coalition framework; multiple streams approach; tobacco act; ministry of health; dutch smoking or health foundation; self-regulation; policy stagnation; the netherlands; tobacco taxation; cultural values; social norms; smoking rate; public support; corporatism; deregulation; evidence based health policy; lobby; agenda setting